(untitled) (Revista Latino-Americana de Enfermagem, 2014)
OBJECTIVE: to analyze assistance regarding contraception methods received by women during hospitalization due to abortion, and contraceptive practices the month after this episode. METHODS: a longitudinal study of women hospitalized due to abortion in a public hospital in the city of São Paulo. Face-to-face interviews (n=170) followed by telephone interviews in the subsequent month (n=147) were conducted between May and December of 2011. RESULTS: a small number of women reported they received guidance on, and prescription for, contraceptive methods at hospital discharge. A trend of statistical significance was identified for prescription of contraceptive methods at discharge and its use in the following month, when adjusted for age. Most women reported sexual intercourse (69.4%) with the use of contraceptive method (82.4%), but no health professional guidance (63.1%). CONCLUSION: despite the fact that post-abortion contraception assistance was lower than the recommended guidelines by public health policies, women demonstrated willingness to use contraceptive methods.